Struktura gledališča v gledališču - Orel, Barbara (Primerjalna književnost, 2001)
Theatre within theatre. - The structure of theatre within theatre, or the play within a play (the most famous instance being the mousetrap in Shakespeare's Hamlet), has been part of drama since the Renaissance, although it was studied theoretically only after 1950. This study reveals the reasons for terminological discrepancies caused by the fundamental research by Joachim Voigt, Erich Proebster, Robert J. Nelson, Jörge H. Kokott and Manfred Schmeling, and on the basis of semiotica categorisation offers suggestions fora typology of this phenomenon.
Keywords: teatrologija; gledališče; theater; dramaturgija; drama; dramatika; igra v igri; gledališče v gledališču; terminologija; terminology